Identifikasi Tingkat Kesadaran Pengguna Mobile Banking terhadap Ancaman Cybercrime - Hutagaol, B. Junedi; Sitorus, Riama Santy; Hutagaol, Nindya (Program Studi Teknik Informatika Universitas Pamulang, 2024)
The development of information technology has brought about a significant increase in the number of people connected to and using the internet. However, this phenomenon also poses serious risks regarding the security of valuable information such as passwords, financial information, and other sensitive data, making them attractive targets for attackers. Attacks on this infrastructure not only have the potential to cause data breaches but also significant financial impacts and even threats to lives. Protecting oneself from these threats, and considering the crucial role of humans in the technology ecosystem, emphasizes the importance of enhancing cybersecurity awareness. This study aims to explore the awareness levels of mobile banking users regarding cybercrime threats, involving the participation of 403 respondents. Questionnaire data processing results showed that 51% of the total respondents have experienced cybercrime attempts, and 21% have been victims. Respondents' awareness levels varied between 3.49 and 4.05 on a Likert scale (1-5). Several factors significantly influence respondents' awareness levels, such as age, occupation, personal experience as a victim of cybercrime attempts, and interactions between variables.